Approach to the state of the art on communication and education in Colombia (2018)
This paper intends to make an approach to the academic production related to the relationship between communication and education that was published in Colombia from 1991 to 2011. The first part comprises the identification of the main theoretical and conceptual approaches addressed in this paper; the second one addresses the issues and problems of interest; and the third one relates to the central axes of the analyzed works, among which the culture, the language, and the codes are fundamental. The research was carried out with a hermeneutical approach, given the interest to understand how the object “communication-education” in Colombia has been understood. In methodological terms, it was decided to make a “state of the art”. The difficulties in specifying the epistemological place in which educommunication is located are among the most important reflections of this review. However, it is recognized that this is a field that has been built more from social practices and ethical-political approaches than from theoretical ones.